2007
DOI: 10.1210/en.2007-0235
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Expression of a Gi-Coupled Receptor in Osteoblasts Results in Trabecular Osteopenia

Abstract: G protein-coupled receptors (GPCRs) coupled to activation of Gs, such as the PTH1 receptor (PTH1R), have long been known to regulate skeletal function and homeostasis. However, the role of GPCRs coupled to other G proteins such as Gi is not well established. We used the tet-off system to regulate the expression of an activated Gi-coupled GPCR (Ro1) in osteoblasts in vivo. Skeletal phenotypes were assessed in mice expressing Ro1 from conception, from late stages of embryogenesis, and after weaning. Long bones w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…Thus, the lesser effect of constitutively active PTHR1 signaling on bone mass (10) may be attributable to PTHR1-induced activation of additional G protein signaling pathways, including G i and G q , that could counteract the anabolic effects of G s activation. Recent studies lend support to this notion, because osteoblast expression of a constitutively active G q ␣ (29) or a constitutively active G icoupled GPCR (26,30) leads to decreased trabecular bone. Mice expressing the constitutively active PTHR1 also show expansion of trabecular bone, with delay of bone marrow cavity formation (31); however, the ColI(2.3)ϩ/Rs1ϩ mice appear to have a more severe phenotype and do not appear to reform a true bone marrow space as they age.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, the lesser effect of constitutively active PTHR1 signaling on bone mass (10) may be attributable to PTHR1-induced activation of additional G protein signaling pathways, including G i and G q , that could counteract the anabolic effects of G s activation. Recent studies lend support to this notion, because osteoblast expression of a constitutively active G q ␣ (29) or a constitutively active G icoupled GPCR (26,30) leads to decreased trabecular bone. Mice expressing the constitutively active PTHR1 also show expansion of trabecular bone, with delay of bone marrow cavity formation (31); however, the ColI(2.3)ϩ/Rs1ϩ mice appear to have a more severe phenotype and do not appear to reform a true bone marrow space as they age.…”
Section: Discussionmentioning
confidence: 95%
“…5C). To obtain spatial control, TetO-Rs1 transgenic mice were mated with transgenic mice expressing tTA under the control of the osteoblast-specific Col1␣-1 2.3-kb promoter fragment (26). In the absence of doxycycline, double transgenic progeny [designated ColI(2.3)ϩ/Rs1ϩ] expressed high levels of Rs1 in whole femurs but not in nonskeletal tissues, as assayed by quantitative real-time PCR (qPCR) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(9) RASSLs no longer respond to endogenous hormones but can be activated by synthetic small-molecule ligands and have proved to be useful for regulating and studying G-protein signaling in several complex systems, including bone. (9,14,15) We further showed that delaying Rs1 expression in Col1(2.3) þ /Rs1 þ until after 4 weeks of age (referred to as Col1/Rs1-late mice herein) significantly attenuates the bone formation phenotype. (15) However, bone formation can be stimulated in these Col1(2.3) þ /Rs1 þ mice by treatment with RS67333, a synthetic serotonin receptor agonist that strongly activates the Rs1 receptor and further increases G s signaling.…”
Section: Introductionmentioning
confidence: 79%
“…Prior studies showed no sexual dimorphism in the bone phenotype, including differences in body length or weight. (9,14,15) All animals in this study were maintained on the FVB/N background and fed a diet containing 200 mg/kg of doxycycline (DoxDiet; Bio-Serv, Frenchtown, NJ, USA) to suppress transgene activity. (14)(15)(16) Delayed expression of Rs1 was activated by switching the mice to regular mouse chow at 4 weeks of age.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation